Content validity for innovation level of UTM undergarduate students: a quantitative approach - Derasid, N. A. C. (Serials Publications, 2016)
Innovation has become one of the vital aspects of a nation's human capital development. Most countries including Malaysia are now putting their best effort to increase their innovation capability in order to be more competitive in various aspects, especially in economy and technology. As one of Malaysian leading universities in engineering and technology, Universiti Teknologi Malaysia (UTM) emphasizes on innovation to all its students by establishing the Centre for Student Innovation (CSI). Its' objectives are to foster and enhance the innovation ability amongst UTM undergraduates. A question rising from this is, 'to what extent this objective has been achieved?' Therefore, it is very important for the UTM-CSI to ensure the effectiveness of their innovative programs that involved undergraduate students. Hence, the aims of this study are to develop and propose an instrument to facilitate UTM-CSI in assessing the level of innovation among UTM undergraduate students. A quantitative approach has been undertaken which includes document analysis from literature review, integration models and theories related to innovation and proposed human capital, and culture and leadership as constructs to develop the instrument in measuring the level of students' innovation. This article will report on the analysis of content validity and reliability using the Fleiss' Kappa Index where the inter-rater agreement on constructs studied is analyzed. The finding shows that the constructs and sub constructs indicated a high degree of agreement values that determine the validity and reliability of the development of instrument.